Minat Belajar Menyanyi Siswa pada Pembelajaran Seni Budaya Siswa Kelas II Sekolah Dasar - Riana Okta Prabandani; E. Sumadiningrat; Eka Yulyawan Kurniawan (AS-SABIQUN, 2022)
This study aims to obtain information about how the interest in learning to sing in second grade elementary school students in learning art and culture at SDN Karanganyar 3, and what factors influence the interest in learning. This research was started from February to August 2022. This study used a qualitative approach and a descriptive type of research. The method used by researchers in this study is a combined method. Data was collected by researchers by observing and interviewing teachers to obtain information about what factors influence interest in learning to sing in second grade students at SDN Karanganyar 3, and distributing questionnaires to grade 2A students to get the results of students' interest in singing. Quantitative data is from the results of questionnaires and is supported by qualitative data from interviews. The results showed that based on indicators of feeling happy students got 85% results, indicators of student interest got 85% results, indicators of student attention reached 81%, and indicators of student participation reached 85%. The results of this questionnaire said that the four indicators were in the category of strongly agree. This is also supported by the results of interviews which stated that the high interest in learning to sing was caused by several factors, namely very adequate school facilities, active and creative teachers, good communication between teachers and parents, parental support, student talents, and students' thinking skills.